2014
DOI: 10.1371/journal.pone.0092164
|View full text |Cite
|
Sign up to set email alerts
|

EDEM2 and OS-9 Are Required for ER-Associated Degradation of Non-Glycosylated Sonic Hedgehog

Abstract: Misfolded proteins of the endoplasmic reticulum (ER) are eliminated by the ER-associated degradation (ERAD) in eukaryotes. In S. cerevisiae, ER-resident lectins mediate substrate recognition through bipartite signals consisting of an unfolded local structure and the adjacent glycan. Trimming of the glycan is essential for the directional delivery of the substrates. Whether a similar recognition and delivery mechanism exists in mammalian cells is unknown. In this study, we systematically study the function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
(82 reference statements)
1
37
1
Order By: Relevance
“…with Z or NHK when the Cys was mutated to a Ser (Fig. 1C, lanes [21][22][23][24], suggesting that the previously observed covalentlike interaction between the misfolded A1AT ERAD variants and EDEM1 involved the single Cys 256 from A1AT.…”
Section: Edem1 Redox-sensitive Binding and Catalytic Activitymentioning
confidence: 69%
See 1 more Smart Citation
“…with Z or NHK when the Cys was mutated to a Ser (Fig. 1C, lanes [21][22][23][24], suggesting that the previously observed covalentlike interaction between the misfolded A1AT ERAD variants and EDEM1 involved the single Cys 256 from A1AT.…”
Section: Edem1 Redox-sensitive Binding and Catalytic Activitymentioning
confidence: 69%
“…Petrescu and co-workers (21) identified an N-terminal IDR that is required for interaction with an unnatural soluble form of tyrosinase, further supporting the nonessential role of the MLD in the interaction between EDEM1 and H2a or soluble tyrosinase. Likewise, the role of glycans in EDEM1 client binding is perplexing and appears substrate-specific as in some cases (NHK, H2a, and SHH) interactions with EDEM1 were independent of substrate glycosylation; however, in other cases glycans appeared required (BACE457) (10,12,20,22). Interactions between EDEM1 and ER machinery-binding partners have been reported and characterized, most notably that the EDEM1 MLD was involved in the interaction with Sel1L as mutating the putative catalytic triad or using mannosidase inhibitors abolished this interaction (10,23).…”
mentioning
confidence: 99%
“…For some substrates, EDEM1 enhances degradation of the glycosylated species but has no effect on the degradation of their non-glycosylated variants 125,126 . Other studies reported a requirement of EDEM1 for degradation of some non-glycosylated protein s as well 127,128 .…”
Section: Glycan-directed Erad In Mammalsmentioning
confidence: 97%
“…Concordantly, the knock-down of EDEM2 acting upstream of EDEM3 in mannose chain trimming [42] has no effect on the expression level of del52 and ins5 mutants. EDEM3, like other members of the EDEM family, has previously been shown to interact with nonglycosylated substrates [43]. However, its role in the degradation of proteins has been limited to glycosylated substrates thus far.…”
Section: Discussionmentioning
confidence: 99%